Gothic Vaulting in Spanish Military Architecture from the Eighteenh Century - Lluis Teruel, Cinta; Lluis i Ginovart, Josep; Ramírez-González, Sergio; Bravo Nieto, Antonio (Springer Nature, 2024)
The construction of gunpowder magazines, undertaken by military engineers in Spain throughout the eighteenth century bears testament to the Enlightenment’s construction ethos in the different domains forming the Hispanic Monarchy. In the study on the typological classification that we have performed on 271 projects involving these magazines, 31 designed using gothic vaults have been unearthed. The geometric study into this constructive system unveils that 68.97% of these pointed arches feature centres placed below the impost, suggesting that the angle of incidence on the vertical faces is below 90º, thus sharing this property with catenary vaults. Viewing the appraisals given in La théorie et la pratique de la coupe de pierres (1738) by Frézier on the structural coherence of these figures, it can be concluded that this pointed system employed by Hispanic military engineers is a simplified attempt to standardise the gothic vault in line with the catenary model.
Política de acceso abierto tomada de: https://openpolicyfinder.jisc.ac.uk/id/publication/15638
Keywords: Arquitectura militar - España; Arte y ciencia militar; Bóvedas góticas; Catenary; Gothic vaults; Gunpowder magazines; Military engineers; Scientific mechanics